Studi Eksperimental Pengaruh Karbon Aktif Terhadap Penyimpanan Biogas - Rapael, Epenetus; Sucipta, Made; Wijaksana, Hendra (Teknik Desain Mekanika; Vol 12 No 4 (2023): Oktober 2023 : Teknik Desain Mekanika, 2023)
Abstract Biogas storage in plastic bags by Simantri farmers in Bali is considered ineffective because plastic is not able to withstand high pressure so the storage capacity is lacking. Adsorbed Natural Gas technology was chosen to store biogas in a higher pressure cylinder with a larger capacity using an adsorbent in the form of activated carbon with a very large surface area. So that the biogas is trapped on the inner surface of the tube and in the pores of the activated carbon. The research was carried out experimentally with 3 main processes, namely the carbonization process at a temperature of 525?C activated at a temperature of 425?C by a steam activation process and the biogas storage test. The activated carbon used has a mesh size of 70-230, a steam flow rate of 100 g/min with a pressure in the boiler of 90 psi and a temperature of 160?C. During the activation process, when it reaches a temperature of 425?C, it is then held for 2 hours. The biogas storage tube contains 15 grams of activated carbon compared to the storage tube without activated carbon. As a result, biogas storage in tubes filled with activated carbon is able to store more biogas with a mass of 35.2 grams compared to tubes without activated carbon, which is only 30.9 grams. Keywords: Activated carbon, biogas, Adsorbed Natural Gas, biogas storage, steam activation